2016
DOI: 10.3390/informatics3030015
|View full text |Cite
|
Sign up to set email alerts
|

Older People Using e-Health Services—Exploring Frequency of Use and Associations with Perceived Benefits for Spouse Caregivers

Abstract: ICT, information-and communication technologies, and e-health services are essential for meeting future care demands. Greater knowledge regarding the implementation of e-health services in long-term care for older people is needed. The purpose of the study was to explore older people's use of e-health services and associations between frequency of use and perceived benefits. In the longitudinal comparative intervention study (n = 65), intervention group participants (n = 42) used an e-health service for 1.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Studies have indicated that digital technology in care changes the role of RNs, which can both reduce and create stress for RNs [26,27]. At the same time, RNs play a significant role in supporting patients' use of digital technology, an activity in which a lack of support pushes patients away [28][29][30]. Taken together, the evidence suggests that RNs are increasingly embracing a professional role that involves using digital technology and necessitates conditions that broaden their area of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that digital technology in care changes the role of RNs, which can both reduce and create stress for RNs [26,27]. At the same time, RNs play a significant role in supporting patients' use of digital technology, an activity in which a lack of support pushes patients away [28][29][30]. Taken together, the evidence suggests that RNs are increasingly embracing a professional role that involves using digital technology and necessitates conditions that broaden their area of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Findings also suggest that ICT medicated support can provide efficient care and save travel costs for caregivers of long-term care patients. Similar interventions with carers of older adults have also shown benefits, for example, in spousal carers [36], [37] -the carers in this scenario being older adults themselves.…”
Section: A Ict Mediation Of Communication In Aged Carementioning
confidence: 98%